Look out, Secret Seven - Blyton, Enid; Ross, Tony (Hodder's Children's Books, an imprint of Hachette Children's Group London, 2015)
What would the Seven do without Scamper the spaniel? First he discovers an unwanted visitor - then he protects the Seven as they spy on a thief late at night in Bramley Woods!